Perbandingan Penanganan Tanah Terlantar di Kabupaten Tasikmalaya dan Kabupaten Sukabumi dalam Mewujudkan Ketahanan Pangan Provinsi Jawa Barat - Ida Nurlinda; Yani Pujiwati; Marenda Ishak (Fakultas Hukum Universitas Islam Indonesia, 2014)
This research discusses the problems of: first, the implementation of the Government Regulation No 11 of 2010 on the Control and Utilization of Deserted Land in Tasikmalaya Regency and Sukabumi Regency; and second, the impact of the implementation of the Government Regulation No 11 of 2010 on the Control and Utilization of Deserted Land on the existence of agricultural land in Tasikmalaya and Sukabumi Regencies to realize the food security. This research used the normative juridical method and analytical descriptive research specification.The study concludes that: first, the Government Regulation No 11 of 2010 is not yet effective to resolve the cases existing in Tasikmalaya and Sukabumi Regencies. This results from the obstacles faced by the Government Regulation No. 11 of 2010 in mapping the land indicated as deserted land since, in fact, the identification and research do not involve the institution authorized forthe determination of the deserted land. Second, the utilization of the deserted land is not yet projected to add and optimize the procurement of agricultural land, so the control of the deserted land has no added value nor strengthens the food security in West Java Province.